Reading a Feminist Response on "The Book of Knowledge" based on Gadamer's Philosophical Hermeneutics - Kodir, Faqihuddin Abdul (DINIKA : Academic Journal of Islamic Studies, 2017)
The position of woman and knowledge in Islamic perspective has been an interesting issue in Islamic studies. One of the female Muslim scholars who focus her studies on feminism is Sa'diyya Shaikh. By exploring Gadamer's philosophical hermeneutics, this paper is aimed at explaining the basic concepts of the philosophical hermeneutics of Sa'diyya Shaikh's "Knowledge, Women, and Gender in the Hadith: a Feminist Interpretation" published in 2014. The work is focused on the interpretation responding to the selected texts of the Hadith in "The Book of Knowledge", the collection of the prophetic traditions by Sahih al-Bukhari. It was found out that prejudice influences Shaikh's motivation in interpreting the text. However, as there are neither merely subjective nor objective aspects in the interpretation, Shaikh positions herself in the structures of self-understanding which reveal "the truth" for her within a horizon. Indeed, Shaikh's interpretation is dynamic. Thus, it can still be fixed and changed to invite new perspectives.